Choosing a Career, Career Guide - Waller T; South Africa (South Africa: Awareness Publishing Group (Pty), 2010)
This Guide can be used on its own to provide a general introduction to he world of work and thinking about suitable careers. it is also designed to accompany the choosing a career series of reading books.
Junior Non-Fiction -;Juvenile Literature